2004
DOI: 10.1097/00020840-200404000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection in the etiology of laryngeal carcinoma

Abstract: An adequately powered, multicenter case-control study is required to elucidate the full extent of this association and to examine the relation between the virus and other risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 29 publications
1
31
0
5
Order By: Relevance
“…[29][30][31] Our results suggest that the onset and progression of HPV-positive carcinomas is indeed distinguishable from their HPV-negative counterparts, particularly in regards to their lack of connection to past tobacco use and earlier onset, while our data are compatible with a possibly better prognosis in terms of recurrence. Similar to other studies, [5][6][7] HPV-16, known to be associated with malignancy, was the most common type detected in positive cases (33.3%). Despite the fact that HPV-6 and -11 are among the most commonly detected types of HPV, neither was found in the laryngeal carcinomas sampled, confirming the role of these two viral types as precursors of mostly benign papillomas rather than malignancies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[29][30][31] Our results suggest that the onset and progression of HPV-positive carcinomas is indeed distinguishable from their HPV-negative counterparts, particularly in regards to their lack of connection to past tobacco use and earlier onset, while our data are compatible with a possibly better prognosis in terms of recurrence. Similar to other studies, [5][6][7] HPV-16, known to be associated with malignancy, was the most common type detected in positive cases (33.3%). Despite the fact that HPV-6 and -11 are among the most commonly detected types of HPV, neither was found in the laryngeal carcinomas sampled, confirming the role of these two viral types as precursors of mostly benign papillomas rather than malignancies.…”
Section: Discussionsupporting
confidence: 88%
“…4 Earlier studies demonstrated that HPV-16 is the most widely detected viral type in cancerous lesions of the larynx, although the reported incidence of HPV varied widely. [5][6][7] Differences in detection methods may account for these inconsistencies, and since most of the assay systems employed were capable of detecting only the most common high-risk HPV types (16,18,31,33, and 45), estimates of incidence may have been conservative. In addition to high-risk HPV as a risk factor for laryngeal malignancies, the presence of low-risk HPV types 6 and 11 has been associated with recurrent respiratory papillomatosis (RRP), which may present with an indolent or aggressive, even life-threatening growth of benign papillomas in the larynx and the airway.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent respiratory papillomas (RRP) represent the most common benign tumor of the larynx, in adults it constitutes about 10% of all laryngeal tumors or about 87% of all benign laryngeal tumors [1][2][3]. The incidence of RRP in the United States is estimated at 4.0-4.3 per 100,000 in children and 1.8-2.0 per 100,000 in adults, 0.24 per 100,000 in children aged 14 years and younger in Canada, and overall incidence at 3.84 cases per 100,000 in Denmark [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Fol lo wing HPV scre e ning, the HPV-po siti ve samp les we re sub mit ted for ge noty ping. The pre vi o usly des cri bed GP-E6/E7 ge noty ping stra tegy, ba sed on MPCR pro duct si ze, was used for HPV ge noty ping.…”
Section: Dna Ex Trac Ti On and Mul Tip Lex Poly Me Ra Se Cha -In Re Amentioning
confidence: 99%